2022
DOI: 10.1155/2022/8703100
|View full text |Cite|
|
Sign up to set email alerts
|

Text Mining Based on the Lexicon-Constrained Network in the Context of Big Data

Abstract: Unstructured textual news data is produced every day; analyzing them using an abstractive summarization algorithm provides advanced analytics to decision-makers. Deep learning network with copy mechanism is finding increasing use in abstractive summarization, because copy mechanism allows sequence-to-sequence models to choose words from the input and put them directly into the output. However, since there is no explicit delimiter in Chinese sentences, most existing models for Chinese abstractive summarization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Wireless Communications and Mobile Computing has retracted the article titled "Text Mining Based on the Lexicon-Constrained Network in the Context of Big Data" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], significant concerns were identified with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
mentioning
confidence: 99%
“…Wireless Communications and Mobile Computing has retracted the article titled "Text Mining Based on the Lexicon-Constrained Network in the Context of Big Data" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], significant concerns were identified with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
mentioning
confidence: 99%